Potent inhibitory action of the gastric proton pump inhibitor lansoprazole against urease activity of Helicobacter pylori: unique action selective for H. pylori cells. - Nagata, K (1993)
The gastric proton pump inhibitor lansoprazole, its active analog AG-2000, and omeprazole dose dependently inhibited urease activity extracted with distilled water from Helicobacter pylori cells; the 50% inhibitory concentrations were between 3.6 and 9.5 microM, which were more potent than those of urease inhibitors, such as acetohydroxamic acid, hydroxyurea, and thiourea. These compounds also inhibited urease activity in intact cells of H. pylori and Helicobacter mustelae but did not inhibit ureases from other bacteria, such as Proteus vulgaris, Proteus mirabilis, and Providencia rettgeri. The mechanism of urease inhibition was considered to be blockage of the SH groups of H. pylori urease, since SH residues in the enzyme decreased after preincubation with lansoprazole and glutathione or dithiothreitol completely abolished the inhibitory action. The SH-blocking reagents N-ethylmaleimide and idoacetamide were also examined for their inhibition of the urease activity; their 50% inhibitory concentrations were 100- to 1,000-fold higher than those of lansoprazole. These results suggest that lansoprazole and omeprazole can potently and selectively inhibit H. pylori urease and that inhibition may be related to earlier findings indicating that these compounds have selective activity against HP growth.